Utilisation of modern contraceptives by sexually active adolescent girls in Rwanda: a nationwide cross-sectional study - Joseph Kawuki; Ghislaine Gatasi; Quraish Sserwanja; David Mukunya; Milton W. Musaba (BMC, 2022)
Abstract Background Modern contraceptive use has been shown to influence population growth, protect women's health and rights, as well as prevent sexually transmitted infections (STIs) for barrier contraceptive methods such as condoms. The present study aimed at assessing the level of utilization and factors associated with modern contraceptive use among sexually active adolescent girls in Rwanda. Methods We used secondary data from the Rwanda Demographic and Health Survey (RDHS) 2020 data of 539 sexually active adolescent girls (aged 15 to 19 years). Multistage stratified sampling was used to select study participants. We conducted multivariable logistic regression to assess the association between various socio-demographics and modern contraceptive use using SPSS version 25. Modern contraception included the use of products or medical procedures that interfere with reproduction from acts of sexual intercourse. Results Of the 539 sexually active girls, only 94 (17.4%, 95% CI: 13.8-20.1) were using modern contraceptives. Implants (69.1%) and male condoms (12.8%) were the most used options. Modern contraceptive use was positively associated with older age (AOR = 10.28, 95% CI: 1.34-78.70), higher educational level (AOR = 6.98, 95% CI: 1.08-45.07), history of having a sexually transmitted infection (AOR = 8.27, 95% CI: 2.54-26.99), working status (AOR = 1.72, 95% CI: 1.03-2.88) and being from a female-headed household (AOR = 1.96, 95% CI: 1.12-3.43). However, not being in a union (AOR = 0.18, 95% CI: 0.10-0.35) and region (AOR = 0.28, 95% CI: 0.10-0.80) had negative associations. Conclusions To promote utilisation of modern contraceptives, family planning campaigns need to place more emphasis on the younger, unmarried adolescents, as well as those with lower educational levels. Consideration of household and regional dynamics is also highlighted.